Anastomotic Outcomes in Military Exploratory Laparotomies in the Modern Combat Era. Issue 4 (April 2022) - Walker, Patrick F.; Bozzay, Joseph D.; Schechtman, David W.; Shaikh, Faraz; Stewart, Laveta; Carson, M. Leigh; Tribble, David R.; Rodriguez, Carlos J.; Bradley, Matthew J.; ,
Background: Intestinal anastomoses in military settings are performed in severely injured patients who often undergo damage control laparotomy in austere environments. We describe anastomotic outcomes of patients from recent wars. Methods: Military personnel with combat-related intra-abdominal injuries (June 2009-December 2014) requiring laparotomy with resection and anastomosis were analyzed. Patients were evacuated from Iraq or Afghanistan to Landstuhl Regional Medical Center (Germany) before being transferred to participating U.S. military hospitals. Results: Among 341 patients who underwent 1053 laparotomies, 87 (25.5%) required ≥1 anastomosis. Stapled anastomosis only was performed in 57.5% of patients, while hand-sewn only was performed in 14.9%, and 9.2% had both stapled and hand-sewn techniques (type unknown for 18.4%). Anastomotic failure occurred in 15% of patients. Those with anastomotic failure required more anastomoses (median 2 anastomoses, interquartile range [IQR] 1-3 vs. 1 anastomosis, IQR 1-2, P = .03) and more total laparotomies (median 5 laparotomies, IQR 3-12 vs. 3, IQR 2-4, P = .01). There were no leaks in patients that had only hand-sewn anastomoses, though a significant difference was not seen with those who had stapled anastomoses. While there was an increasing trend regarding surgical site infections (SSIs) with anastomotic failure after excluding superficial SSIs, it was not significant. There was no difference in mortality. Discussion: Military trauma patients have a similar anastomotic failure rate to civilian trauma patients. Patients with anastomotic failure were more likely to have had more anastomoses and more total laparotomies. No definitive conclusions can be drawn about anastomotic outcome differences between hand-sewn and stapled techniques.